A method for preparing a woven fabric-based cellulose-amino acid composite diaphragm
Through the preparation method of woven fabric-based cellulose-amino acid composite separator, the existing separator mechanical properties and poor wetting properties are solved, high mechanical strength and good electrolyte retention capabilities are achieved, cost is reduced, and it is suitable for large-scale industrial applications, improving the stability and safety of the battery.
Patent Information
- Application Number
- CN202410105907.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-25
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-01-25
AI Technical Summary
The existing battery separators have poor mechanical properties and electrolyte wetting properties, high costs, which are not conducive to large-scale industrial applications, nor are they conducive to battery stability and safety.
Using the preparation method of a woven fabric-based cellulose-amino acid composite separator, a polypropylene filament yarn weaving woven fabric substrate is used to dissolve cellulose in combination with ionic liquid, and a mixture of cellulose and amino acids is uniformly deposited on the substrate, and a composite separator is obtained by displacing deionized water and freeze-dried.
It realizes the high mechanical strength of the diaphragm and good electrolyte retention ability, reduces costs, is suitable for large-scale industrial applications, and improves the cycle stability and safety of the battery.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of energy storage material preparation, and in particular to a method for preparing a woven fabric-based cellulose-amino acid composite diaphragm. Background Art
[0002] The frequent occurrence of battery fires nowadays has made safety performance a key concern for people. When the battery is working, due to the uneven electric field distribution and ion deposition, uncontrollable dendrite growth occurs at the negative electrode, which then pierces the low-strength separator, causing a short circuit between the positive and negative electrodes. In severe cases, there may be a safety hazard of battery explosion and fire.
[0003] The diaphragm is an important component in the battery, which serves to isolate the positive and negative electrodes to prevent short circuits and ensure ion transmission. Its material and structure have a huge impact on the stability and safety of the battery.
[0004] At present, the commonly used raw materials for diaphragms are glass fiber and polyolefin diaphragms. Among them, the glass fiber diaphragms commonly used in laboratories have poor mechanical properties and high costs, while the commercial polyolefin diaphragms have poor electrolyte wettability and high temperature resistance. Both are not conducive to large-scale industrial applications, nor are they conducive to the stability and safety of batteries. Summary of the invention
[0005] 1. Technical issues to be solved
[0006] The purpose of the present invention is to solve the problems of poor mechanical properties and electrolyte wettability of the diaphragm, high cost and disadvantageous for large-scale industrialization in the prior art, and to propose a method for preparing a woven fabric-based cellulose-amino acid composite diaphragm.
[0007] 2. Technical solution
[0008] In order to achieve the above object, the present invention adopts the following technical solutions:
[0009] A method for preparing a woven fabric-based cellulose-amino acid composite membrane comprises the following steps:
[0010] Step 1: Using polypropylene filament yarn as raw material, weave woven fabrics with different organizational structures on a sample loom as a composite diaphragm substrate;
[0011] Step 2: After the weaving is completed, the fabric is soaked in ethanol and acetone and dried at room temperature;
[0012] Step 3: completely dissolving cellulose in the ionic liquid, adding amino acids to the cellulose slurry, and mixing them thoroughly to prepare a filler for the composite diaphragm;
[0013] Step 4: Place the filler on the surface of the woven fabric, use an applicator to evenly apply it to the woven fabric substrate, and let it stand until it is fully deposited in the pore structure of the substrate;
[0014] Step 5: immersing the composite fabric obtained in step 4 in deionized water and performing repeated replacement treatment to remove the ionic liquid in step 3;
[0015] Step 6: Place the composite fabric replaced in step 5 in a freeze dryer to remove moisture and dry, thereby obtaining the above-mentioned woven fabric-based cellulose-amino acid composite membrane.
[0016] Preferably, in step 1, the raw material of the woven fabric base is generally selected from polypropylene filament yarn with a wicking effect. The fineness of the polypropylene filament yarn can be adjusted according to the requirements of the sample loom.
[0017] Preferably, in step 1, the weave structure of the woven fabric base includes all basic weaves, variable weaves, combined weaves and complex weaves.
[0018] Preferably, in step 3, the research objects of the filler are all celluloses and amino acids; cellulose includes all celluloses and their derivatives. In order to accelerate the dissolution of cellulose and enrich the types of membrane functional groups, carboxylation of cellulose is the key; considering the deposition effect of the filler, amino acids with a relatively small molecular weight are generally selected to reduce the viscosity of the filling mixture.
[0019] Preferably, in step 3, the solvent is generally an ionic liquid capable of dissolving cellulose. Ionic liquid solvents include but are not limited to 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium chloride, and the like.
[0020] Preferably, in step 3, the mass ratio of cellulose to amino acids in the sediment can be 1:1, 1:2 and 2:1; and the dissolution temperature can be 60-90°C.
[0021] Preferably, in step 4, the coating thickness is generally above 100 μm.
[0022] Preferably, in step 5, deionized water is generally used to replace the ionic liquid, and the replacement is repeated until the ionic liquid is completely removed.
[0023] The present invention also proposes the use of a woven fabric-based cellulose-amino acid composite membrane in regulating uniform ion deposition, improving coulombic efficiency, and extending battery cycle life.
[0024] 3. Beneficial effects
[0025] Compared with the prior art, the advantages of the present invention are:
[0026] (1) In the present invention, a battery separator is prepared by coating and other processes using woven fabric as a substrate, cellulose and amino acids as fillers. During the weaving process of the woven fabric substrate, the orderly interlacing of warp and weft yarns is used to achieve the design of the pore structure and curvature of the separator, and an efficient ion transmission channel is established inside the battery. The interaction between the warp and weft yarns enhances the mechanical strength of the substrate without losing flexibility, which plays a good role in resisting dendrite puncture during battery cycling.
[0027] (2) In the present invention, the addition of filling materials such as cellulose and amino acids, on the one hand, optimizes the physical structure of the diaphragm, fills the macroporous structure of the fabric, and improves the diaphragm's ability to retain electrolytes; on the other hand, the functional groups such as the hydroxyl groups of cellulose and the amino groups of amino acids give the diaphragm electronegativity, which will accelerate the migration of positive ions; finally, the types and contents of the polar functions of the diaphragm are enriched, and the cycle stability of the battery is improved and the cycle life of the battery is extended through uniform electric field distribution and ion concentration.
[0028] (3) In the present invention, the preparation method is applicable to all woven fabrics, cellulose and amino acids, and they can all be used to prepare membranes with excellent properties through the preparation method of the present invention.
[0029] (4) In the present invention, the preparation method limits the dissolution temperature of cellulose and amino acids, fully ensuring the dissolution effect while avoiding the influence of excessively high temperature on the performance of amino acids; the membrane preparation process is simple, low-cost, and the raw materials used are green and environmentally friendly, and it is expected to achieve mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The following four figures are listed to illustrate the performance of the composite diaphragm in Example 4.
[0031] Figure 1 The infrared spectrum of the diaphragm prepared by the method of the present invention using polypropylene, carboxylated cellulose and glycine as raw materials;
[0032] Figure 2 The electrolyte contact angle of the diaphragm prepared by the method of the present invention using polypropylene, carboxylated cellulose and glycine as raw materials;
[0033] Figure 3 Deposition and stripping curves of the separator prepared by the method of the present invention using polypropylene, carboxylated cellulose and glycine as raw materials in a sodium symmetric battery;
[0034] Figure 4 The present invention discloses a cycle curve of a diaphragm in a sodium ion battery using polypropylene, carboxylated cellulose and glycine as raw materials and the prepared diaphragm using the method of the present invention. DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0036] Embodiment 1:
[0037] A method for preparing a woven fabric-based cellulose-amino acid composite membrane comprises the following steps:
[0038] Step 1. To ensure the mechanical strength of the substrate, 300 denier (approximately 300-320 μm in diameter) polypropylene filament yarn is used as the raw material to weave a plain weave woven fabric substrate on a sample loom. Polypropylene filament yarn is selected for the following reasons: light weight, which is beneficial to the improvement of battery mass energy density; high mechanical strength, as a substrate can resist dendrite puncture to a certain extent; it has a wicking effect, which helps the rapid penetration of electrolyte. The plain weave is selected as the organizational structure of the woven fabric substrate because the plain weave warp and weft yarns are interwoven every other yarn, and the mechanical strength is the highest among all organizational structures, which can effectively resist dendrite puncture.
[0039] Step 2, preparing a mixed solution according to the mass ratio of ionic liquid: carboxylated cellulose: glycine of 75:1:1, and heating at 80°C to completely dissolve the cellulose and amino acid; the ionic liquid used is 1-ethyl-3-methyl-imidazolium chloride; the ionic liquid can break the hydrogen bonds of the carboxylated cellulose and completely dissolve it; the hydroxyl and carboxyl groups of the carboxylated cellulose are hydrogen-bonded with the amino groups of glycine; the low relative molecular mass of glycine can effectively reduce the viscosity of the mixed solution and improve the deposition effect;
[0040] Step 3, the fabric substrate pre-treated with ethanol and acetone is placed on a glass plate, and the mixed solution is evenly deposited on the substrate using an applicator; the carboxylated cellulose and glycine in the mixed solution contain abundant polar functional groups, such as hydroxyl, carboxyl, and amino groups, which can effectively even out the ion flux and induce even ion deposition; the polar functional groups are beneficial to the improvement of the solvent affinity of the diaphragm electrolyte; the negatively charged polar functional groups give the diaphragm negative charge, which is beneficial to the transmission of ions;
[0041] Step 4, adding deionized water and soaking repeatedly to displace the ionic liquid, and freeze-drying to obtain a woven fabric-based cellulose-amino acid composite diaphragm; the addition of cellulose and amino acids can fill the macroporous structure of the fabric substrate, which helps to improve the electrolyte retention rate of the diaphragm;
[0042] In this embodiment, a battery separator is prepared by coating and other processes using woven fabric as a substrate, cellulose and amino acids as filling materials. During the weaving process of the woven fabric substrate, the orderly interlacing of warp and weft yarns is used to achieve the design of the pore structure and curvature of the separator, and an efficient ion transmission channel is established inside the battery. The interaction between the warp and weft yarns enhances the mechanical strength of the substrate without losing flexibility, and plays a good role in resisting dendrite puncture during battery cycling. The addition of filling materials cellulose and amino acids, on the one hand, optimizes the pore structure of the separator, fills the macroporous structure of the fabric, and improves the separator's ability to retain electrolytes; on the other hand, the functional groups such as hydroxyl groups of cellulose and amino acids give the separator electronegativity, which will accelerate the migration of positive ions; finally, the types and contents of polar functional groups of the separator are enriched, and the cycle stability of the battery is improved and the cycle life of the battery is extended through uniform electric field distribution and ion concentration.
[0043] In this embodiment, the preparation method is applicable to all woven fabrics, cellulose and amino acids, and they can all be used to prepare membranes with excellent performance through the preparation method of the present invention.
[0044] In this embodiment, the preparation method limits the dissolution temperature of cellulose and amino acids, fully ensuring the dissolution effect while avoiding the influence of excessive temperature on the performance of amino acids; the membrane preparation process is simple, low-cost, and the raw materials used are green and environmentally friendly, and it is expected to achieve mass production.
[0045] Embodiment 2:
[0046] It has the implementation content of the above-mentioned embodiment, wherein the specific implementation of the above-mentioned embodiment can refer to the above description, and the embodiment here will not be repeated in detail; and in the embodiment of the present application, it is different from the above-mentioned embodiment in that:
[0047] Step 1, use 300 denier (diameter is about 300-320μm) polypropylene filament yarn as raw material to weave a twill weave woven fabric base on a sample loom. The reasons for choosing polypropylene filament yarn are as follows: light weight, which is beneficial to the improvement of battery mass energy density; high mechanical strength, as a base can resist dendrite puncture to a certain extent; it has a wicking effect, which helps the rapid penetration of electrolyte. The twill weave is chosen as the organizational structure of the woven fabric base because the twill weave yarn density is higher and the force between the warp and weft yarns is stronger, so the porosity of the base is higher and can accommodate more electrolyte.
[0048] Step 2, preparing a mixed solution according to the mass ratio of ionic liquid: carboxylated cellulose: glycine of 75:1:1, and heating at 80°C to completely dissolve the cellulose and amino acid; the ionic liquid used is 1-ethyl-3-methyl-imidazolium chloride; the ionic liquid can break the hydrogen bonds of the carboxylated cellulose and completely dissolve it; the hydroxyl and carboxyl groups of the carboxylated cellulose are hydrogen-bonded with the amino groups of glycine; the low relative molecular mass of glycine can effectively reduce the viscosity of the mixed solution and improve the deposition effect;
[0049] Step 3, the fabric substrate pre-treated with ethanol and acetone is placed on a glass plate, and the mixed solution is evenly deposited on the substrate using an applicator; the carboxylated cellulose and glycine in the mixed solution contain abundant polar functional groups, such as hydroxyl, carboxyl, and amino groups, which can effectively even out the ion flux and induce even ion deposition; the polar functional groups are beneficial to the improvement of the solvent affinity of the diaphragm electrolyte; the negatively charged polar functional groups give the diaphragm negative charge, which is beneficial to the transmission of ions;
[0050] Step 4, adding deionized water for repeated soaking to displace the ionic liquid, and then freeze-drying to obtain a woven fabric-based cellulose-amino acid composite diaphragm; the addition of cellulose and amino acids can fill the macroporous structure of the fabric base, which helps to improve the electrolyte retention rate of the diaphragm.
[0051] Embodiment 3:
[0052] It has the implementation content of the above-mentioned embodiment, wherein the specific implementation of the above-mentioned embodiment can refer to the above description, and the embodiment here will not be repeated in detail; and in the embodiment of the present application, it is different from the above-mentioned embodiment in that:
[0053] Step 1, use 300 denier (diameter is about 300-320μm) polypropylene filament yarn as raw material, and weave a satin weave woven fabric base on a sample loom. The reasons for choosing polypropylene filament yarn are as follows: light weight, which is beneficial to the improvement of battery mass energy density; high mechanical strength, as a base can resist dendrite puncture to a certain extent; it has a wicking effect, which helps the rapid penetration of electrolyte. The satin weave is chosen as the organizational structure of the woven fabric base because there are floating long lines on the surface of the satin weave, and the base exhibits a smooth feature. Using it in the battery can minimize the interface problems between the diaphragm and the electrode.
[0054] Step 2, preparing a mixed solution according to the mass ratio of ionic liquid: carboxylated cellulose: glycine of 75:1:1, and heating at 80°C to completely dissolve the cellulose and amino acid; the ionic liquid used is 1-ethyl-3-methyl-imidazolium chloride; the ionic liquid can break the hydrogen bonds of the carboxylated cellulose and completely dissolve it; the hydroxyl and carboxyl groups of the carboxylated cellulose are hydrogen-bonded with the amino groups of glycine; the low relative molecular mass of glycine can effectively reduce the viscosity of the mixed solution and improve the deposition effect;
[0055] Step 3, the fabric substrate pre-treated with ethanol and acetone is placed on a glass plate, and the mixed solution is evenly deposited on the substrate using an applicator; the carboxylated cellulose and glycine in the mixed solution contain abundant polar functional groups, such as hydroxyl, carboxyl, and amino groups, which can effectively even out the ion flux and induce even ion deposition; the polar functional groups are beneficial to the improvement of the solvent affinity of the diaphragm electrolyte; the negatively charged polar functional groups give the diaphragm negative charge, which is beneficial to the transmission of ions;
[0056] Step 4, adding deionized water for repeated soaking to displace the ionic liquid, and then freeze-drying to obtain a woven fabric-based cellulose-amino acid composite diaphragm; the addition of cellulose and amino acids can fill the macroporous structure of the fabric base, which helps to improve the electrolyte retention rate of the diaphragm.
[0057] Embodiment 4:
[0058] It has the implementation content of the above-mentioned embodiment, wherein the specific implementation of the above-mentioned embodiment can refer to the above description, and the embodiment here will not be repeated in detail; and in the embodiment of the present application, it is different from the above-mentioned embodiment in that:
[0059] Step 1, using 300 denier (approximately 300-320 μm in diameter) polypropylene filament yarn as raw material, weave a square weave woven fabric base on a sample loom. The reasons for choosing polypropylene filament yarn are as follows: light weight, which is beneficial to the improvement of battery mass energy density; high mechanical strength, as a base can resist dendrite puncture to a certain extent; it has a wicking effect, which helps the rapid penetration of electrolyte. The square weave is chosen as the organizational structure of the woven fabric base, on the one hand, because the tissue has a large specific surface area, can deposit more cellulose and amino acids, and provide abundant electrolyte occupation sites; on the other hand, the curvature of the square weave is smaller, which reduces the resistance to ion movement and migration from a microscopic perspective, and effectively promotes the ion transmission dynamics.
[0060] Step 2, preparing and mixing ionic liquid: carboxylated cellulose: glycine in a mass ratio of 75:1:1, and heating at 80°C to completely dissolve the cellulose and amino acid; the ionic liquid used is 1-ethyl-3-methyl-imidazolium chloride; the ionic liquid can break the hydrogen bonds of the carboxylated cellulose and completely dissolve it; the hydroxyl and carboxyl groups of the carboxylated cellulose are hydrogen-bonded with the amino groups of glycine; the low relative molecular mass of glycine can effectively reduce the viscosity of the mixed solution and improve the deposition effect;
[0061] Step 3, the fabric substrate pre-treated with ethanol and acetone is placed on a glass plate, and the sediment mixture is evenly deposited on the substrate using an applicator; the carboxylated cellulose and glycine in the mixture contain abundant polar functional groups, such as hydroxyl, carboxyl, and amino groups, which can effectively even out the ion flux and induce uniform ion deposition; the polar functional groups are beneficial to the improvement of the solvent affinity of the diaphragm electrolyte; the negatively charged polar functional groups give the diaphragm negative charge, which is beneficial to the transmission of ions;
[0062] Step 4, adding deionized water for repeated soaking to displace the ionic liquid, and then freeze-drying to obtain a woven fabric-based cellulose-amino acid composite diaphragm; the addition of cellulose and amino acids can fill the macroporous structure of the fabric base, which helps to improve the electrolyte retention rate of the diaphragm.
[0063] Embodiment 5:
[0064] It has the implementation content of the above-mentioned embodiment, wherein the specific implementation of the above-mentioned embodiment can refer to the above description, and the embodiment here will not be repeated in detail; and in the embodiment of the present application, it is different from the above-mentioned embodiment in that:
[0065] Step 1, using 300 denier (approximately 300-320 μm in diameter) polypropylene filament yarn as raw material, weave a square weave woven fabric base on a sample loom. The reasons for choosing polypropylene filament yarn are as follows: light weight, which is beneficial to the improvement of battery mass energy density; high mechanical strength, as a base can resist dendrite puncture to a certain extent; it has a wicking effect, which helps the rapid penetration of electrolyte. The square weave is chosen as the organizational structure of the woven fabric base, on the one hand, because the tissue has a large specific surface area, can deposit more cellulose and amino acids, and provide abundant electrolyte occupation sites; on the other hand, the curvature of the square weave is smaller, which reduces the resistance to ion movement and migration from a microscopic perspective, and effectively promotes the ion transmission dynamics.
[0066] Step 2, preparing a mixed solution according to the mass ratio of ionic liquid: carboxylated cellulose: glycine of 75:1:2, and heating at 80°C to completely dissolve the cellulose and amino acid; the ionic liquid used is 1-ethyl-3-methyl-imidazolium chloride; the ionic liquid can break the hydrogen bonds of the carboxylated cellulose and completely dissolve it; the hydroxyl and carboxyl groups of the carboxylated cellulose are hydrogen-bonded with the amino groups of glycine; the low relative molecular mass of glycine can effectively reduce the viscosity of the mixed solution and improve the deposition effect;
[0067] Step 3, the fabric substrate pre-treated with ethanol and acetone is placed on a glass plate, and the mixed solution is evenly deposited on the substrate using an applicator; the carboxylated cellulose and glycine in the mixed solution contain abundant polar functional groups, such as hydroxyl, carboxyl, and amino groups, which can effectively even out the ion flux and induce even ion deposition; the polar functional groups are beneficial to the improvement of the solvent affinity of the diaphragm electrolyte; the negatively charged polar functional groups give the diaphragm negative charge, which is beneficial to the transmission of ions;
[0068] Step 4, adding deionized water for repeated soaking to displace the ionic liquid, and then freeze-drying to obtain a woven fabric-based cellulose-amino acid composite diaphragm; the addition of cellulose and amino acids can fill the macroporous structure of the fabric base, which helps to improve the electrolyte retention rate of the diaphragm.
[0069] Embodiment 6:
[0070] It has the implementation content of the above-mentioned embodiment, wherein the specific implementation of the above-mentioned embodiment can refer to the above description, and the embodiment here will not be repeated in detail; and in the embodiment of the present application, it is different from the above-mentioned embodiment in that:
[0071] Step 1, using 300 denier (approximately 300-320 μm in diameter) polypropylene filament yarn as raw material, weave a square weave woven fabric base on a sample loom. The reasons for choosing polypropylene filament yarn are as follows: light weight, which is beneficial to the improvement of battery mass energy density; high mechanical strength, as a base can resist dendrite puncture to a certain extent; it has a wicking effect, which helps the rapid penetration of electrolyte. The square weave is chosen as the organizational structure of the woven fabric base, on the one hand, because the tissue has a large specific surface area, can deposit more cellulose and amino acids, and provide abundant electrolyte occupation sites; on the other hand, the curvature of the square weave is smaller, which reduces the resistance to ion movement and migration from a microscopic perspective, and effectively promotes the ion transmission dynamics.
[0072] Step 2, preparing a mixed solution according to the mass ratio of ionic liquid: carboxylated cellulose: glycine of 75:2:1, and heating at 80°C to completely dissolve the cellulose and amino acid; the ionic liquid used is 1-ethyl-3-methyl-imidazole chloride; the ionic liquid can break the hydrogen bonds of the carboxylated cellulose, so that the hydroxyl and carboxyl groups of the carboxylated cellulose are completely dissolved and hydrogen-bonded with the amino groups of glycine; the low relative molecular mass of glycine can effectively reduce the viscosity of the mixed solution and improve the deposition effect;
[0073] Step 3, the fabric substrate pre-treated with ethanol and acetone is placed on a glass plate, and the mixed solution is evenly deposited on the substrate using an applicator; the carboxylated cellulose and glycine in the mixed solution contain abundant polar functional groups, such as hydroxyl, carboxyl, and amino groups, which can effectively even out the ion flux and induce even ion deposition; the polar functional groups are beneficial to the improvement of the solvent affinity of the diaphragm electrolyte; the negatively charged polar functional groups give the diaphragm negative charge, which is beneficial to the transmission of ions;
[0074] Step 4, adding deionized water for repeated soaking to displace the ionic liquid, and then freeze-drying to obtain a woven fabric-based cellulose-amino acid composite diaphragm; the addition of cellulose and amino acids can fill the macroporous structure of the fabric base, which helps to improve the electrolyte retention rate of the diaphragm.
[0075] Embodiment 7:
[0076] It has the implementation content of the above-mentioned embodiment, wherein the specific implementation of the above-mentioned embodiment can refer to the above description, and the embodiment here will not be repeated in detail; and in the embodiment of the present application, it is different from the above-mentioned embodiment in that:
[0077] Step 1, using 300 denier (approximately 300-320 μm in diameter) polypropylene filament yarn as raw material, weave a square weave woven fabric base on a small sample loom. The reasons for choosing polypropylene filament are as follows: light weight, which is beneficial to the improvement of battery mass energy density; high mechanical strength, as a base can resist dendrite puncture to a certain extent; it has a wicking effect, which helps the rapid penetration of electrolyte. The square weave is chosen as the organizational structure of the woven fabric base, on the one hand, because the tissue has a large specific surface area, can deposit more cellulose and amino acids, and provide abundant electrolyte occupation sites; on the other hand, the curvature of the square weave is smaller, which reduces the resistance to ion movement and migration from a microscopic perspective, and effectively promotes the ion transmission dynamics.
[0078] Step 2, preparing a mixed solution according to the mass ratio of ionic liquid: carboxylated cellulose: serine of 75:1:1, and heating at 80°C to completely dissolve the cellulose and amino acid; the ionic liquid used is 1-ethyl-3-methyl-imidazolium chloride; the ionic liquid can break the hydrogen bonds of the carboxylated cellulose and completely dissolve it; the hydroxyl and carboxyl groups of the carboxylated cellulose are hydrogen-bonded with the amino group of glycine; the low relative molecular mass of glycine can effectively reduce the viscosity of the mixed solution and improve the deposition effect;
[0079] Step 3, the fabric substrate pre-treated with ethanol and acetone is placed on a glass plate, and the mixed solution is evenly deposited on the substrate using an applicator; the carboxylated cellulose and glycine in the mixed solution contain abundant polar functional groups, such as hydroxyl, carboxyl, and amino groups, which can effectively even out the ion flux and induce even ion deposition; the polar functional groups are beneficial to the improvement of the solvent affinity of the diaphragm electrolyte; the negatively charged polar functional groups give the diaphragm negative charge, which is beneficial to the transmission of ions;
[0080] Step 4, adding deionized water for repeated soaking to displace the ionic liquid, and then freeze-drying to obtain a woven fabric-based cellulose-amino acid composite diaphragm; the addition of cellulose and amino acids can fill the macroporous structure of the fabric base, which helps to improve the electrolyte retention rate of the diaphragm.
[0081] Embodiment 8:
[0082] It has the implementation content of the above-mentioned embodiment, wherein the specific implementation of the above-mentioned embodiment can refer to the above description, and the embodiment here will not be repeated in detail; and in the embodiment of the present application, it is different from the above-mentioned embodiment in that:
[0083] Step 1, using 300 denier (approximately 300-320 μm in diameter) polypropylene filament yarn as raw material, weave a square weave woven fabric base on a sample loom. The reasons for choosing polypropylene filament yarn are as follows: light weight, which is beneficial to the improvement of battery mass energy density; high mechanical strength, as a base can resist dendrite puncture to a certain extent; it has a wicking effect, which helps the rapid penetration of electrolyte. The square weave is chosen as the organizational structure of the woven fabric base, on the one hand, because the tissue has a large specific surface area, can deposit more cellulose and amino acids, and provide abundant electrolyte occupation sites; on the other hand, the curvature of the square weave is smaller, which reduces the resistance to ion movement and migration from a microscopic perspective, and effectively promotes the ion transmission dynamics.
[0084] Step 2, preparing a mixed solution according to the mass ratio of ionic liquid: carboxylated cellulose: alanine of 75:1:1, and heating at 80°C to completely dissolve the cellulose and amino acid; the ionic liquid used is 1-ethyl-3-methyl-imidazolium chloride; the ionic liquid can break the hydrogen bonds of the carboxylated cellulose and completely dissolve it; the hydroxyl and carboxyl groups of the carboxylated cellulose are hydrogen-bonded with the amino group of glycine; the low relative molecular mass of glycine can effectively reduce the viscosity of the mixed solution and improve the deposition effect;
[0085] Step 3, the fabric substrate pre-treated with ethanol and acetone is placed on a glass plate, and the mixed solution is evenly deposited on the substrate using an applicator; the carboxylated cellulose and glycine in the mixed solution contain abundant polar functional groups, such as hydroxyl, carboxyl, and amino groups, which can effectively even out the ion flux and induce even ion deposition; the polar functional groups are beneficial to the improvement of the solvent affinity of the diaphragm electrolyte; the negatively charged polar functional groups give the diaphragm negative charge, which is beneficial to the transmission of ions;
[0086] Step 4, adding deionized water for repeated soaking to displace the ionic liquid, and then freeze-drying to obtain a woven fabric-based cellulose-amino acid composite diaphragm; the addition of cellulose and amino acids can fill the macroporous structure of the fabric base, which helps to improve the electrolyte retention rate of the diaphragm.
[0087] like Figure 1 The addition of cellulose and amino acids in the woven fabric base enriches the content and types of membrane functional groups.
[0088] like Figure 2 The woven fabric-based cellulose-amino acid separator has excellent electrolyte wettability and excellent affinity for the electrolyte. The electrolyte contact angle is 0° at 0.5S.
[0089] like Figure 3 , comparison of the deposition and peeling curves of the Na-Na symmetric battery corresponding to the woven fabric-based cellulose-amino acid composite membrane of the present invention and the commercial polyolefin PP. The woven fabric-based cellulose-amino acid composite membrane of the present invention can stably deposit and peel for more than 2500 hours, and the overpotential is maintained at 60mV without obvious changes. However, the commercial polyolefin PP membrane experienced a sudden increase in overpotential less than 500 hours ago, that is, the battery was severely polarized. The commercial PP membrane has low mechanical strength, and dendrites can easily pierce the membrane, causing the battery to polarize. The woven fabric-based cellulose-amino acid composite membrane of the present invention has high mechanical strength and can effectively resist the piercing of dendrites; more importantly, the cellulose and glycine introduced into the woven fabric substrate give the membrane rich polar functional groups, which can fundamentally uniform the electric field distribution and ion deposition, and inhibit the formation of dendrites.
[0090] like Figure 4 The cycling curve of a half-cell assembled with sodium foil and hard carbon material as electrodes and the woven fabric-based cellulose-amino acid composite diaphragm of the present invention at a current density of 0.1C is shown. During the cycling process, the coulombic efficiency of the diaphragm is always maintained above 99%, showing excellent cycling stability. At 75 cycles, the capacity of the battery is still maintained at 300mAh g -1 The above results in a highly stable battery cycle.
[0091] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a woven fabric-based cellulose-amino acid composite membrane, characterized in that: The following steps are involved: Step 1: Using polypropylene filament yarn as raw material, weave plain weave, twill weave, satin weave or basket weave on a sample loom as a composite diaphragm base; Step 2: After the weaving is completed, the fabric is soaked in ethanol and acetone and dried at room temperature; Step 3: completely dissolving cellulose in the ionic liquid at a dissolution temperature of 60-90°C, adding amino acids to the cellulose slurry and mixing them thoroughly to prepare a filler for the composite diaphragm; the amino acid is glycine to reduce the viscosity of the filling mixture; Step 4: Place the filler on the surface of the woven fabric, use an applicator to evenly apply it to the woven fabric substrate, and let it stand until it is fully deposited in the pore structure of the substrate; Step 5: immersing the composite fabric obtained in step 4 in deionized water and performing repeated replacement treatment to remove the ionic liquid in step 3; Step 6: Place the composite fabric replaced in step 5 in a freeze dryer to remove moisture and dry, thereby obtaining the above-mentioned woven fabric-based cellulose-amino acid composite membrane.
2. The method for preparing a woven fabric-based cellulose-amino acid composite membrane according to claim 1, characterized in that: The polypropylene filament yarn in step 1 is a polypropylene filament yarn with a wicking effect, and the fineness of the polypropylene filament yarn can be adjusted according to the machine requirements of the sample loom.
3. The method for preparing a woven fabric-based cellulose-amino acid composite membrane according to claim 1, characterized in that: In the step 3, the cellulose includes all cellulose and its derivatives.
4. The method for preparing a woven fabric-based cellulose-amino acid composite membrane according to claim 1, characterized in that: In the step 3, the ionic liquid solvent includes 1-ethyl-3-methylimidazolium tetrafluoroborate and 1-ethyl-3-methylimidazolium chloride.
5. The method for preparing a woven fabric-based cellulose-amino acid composite membrane according to claim 1, characterized in that: The mass ratio of cellulose to amino acids in the filler is 1:1, 1:2 or 2:
1.
6. The method for preparing a woven fabric-based cellulose-amino acid composite membrane according to claim 1, characterized in that: In step 4, the coating thickness is greater than 100 μm.
7. The method for preparing a woven fabric-based cellulose-amino acid composite membrane according to claim 1, characterized in that: In step 5, the ionic liquid is replaced with deionized water, and the replacement is repeated until the ionic liquid is completely removed.
8. Use of the woven fabric-based cellulose-amino acid composite membrane prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The diaphragm is used in regulating uniform ion deposition, improving coulombic efficiency and extending battery cycle life.
Citation Information
Patent Citations
Modified bacterial cellulose lithium-sulfur battery diaphragm
CN112054148A
Cellulose carbamate spinning solution, method for producing a cellulose carbamate nonwoven, and use of the same
US20090258561A1